Searching for Biomarkers in Proliferative Diabetic Retinopathy: Amphiregulin and Progranulin - Burak BILGIN; Mete GULER; Hulya CICEK; Selma URFALIOGLU; Gokhan KOKUSARI; Bedia MARANGOZOGLU SAHIN (Medeniyet Medical Journal)
Objective: Diabetic retinopathy is a common diabetic microvascular problem. Its diagnosis and classification are based on visible changes in clinical fundus examination. However, the discovery of possible vitreous biomarkers in patients with proliferative and nonproliferative diabetic retinopathy may guide both the differentiation and degree of retinopathy. Biomarkers that will be accepted can be also a treatment target. Amphiregulin (AREG) promotes proliferative and regenerative activity and repairs most cell types by binding and activating epidermal growth factor receptors. Progranulin (PGRN) has complex functions in many physiological and pathological processes. Thus, this study aimed to report vitreous AREG and PGRN levels in patients with diabetes and proliferative retinopathy and compare the results with those without diabetes. Methods: Thirty-three eyes of 33 patients with proliferative diabetic retinopathy and 31 eyes of 31 patients without diabetes were included in this study. Vitreous humor samples were collected from all patients at the time of pars plana vitrectomy surgery immediately before the surgical procedure. Vitreous AREG and PGRN values were determined by the ELISA method. Results: The mean AREG and PGRN values were similar in the groups (p=0.427, p=0.459, respectively). Conclusions: The results demonstrated that vitreous AREG and PGRN levels have no significant relationship with proliferative diabetic retinopathy.